IMMUNOPATHOLOGY OF AMOEBIASIS IN IBADAN (1971)
Amoebiasis exemplifies a disease of protean manifestations which presents many perplexing problems. In this thesis an attempt is made to define a number of the wide variations which have been observed in the pathological manifestations of the disease. The work consists of both retrospective and prospective Studies. The retrospective study involved a review of the 7922 protocols of the autopsies at the University College Hospital, Ibadan, during the ten year period 1958 to 1967. 135 cases in which lesions of amoebiasis were described, were selected for special study using 276 cases of other diarrhoeal diseases as controls. The results of this review defined the pathology and complications of amoebiasis seen at the UCH, during the period covered by this study. A prospective study which included field surveys. laboratory studies on patients and controls; and in-vitro studies of the parasite was also carried out. Parasitological, biochemical and immunological techniques were applied in the prospective study of 1291 subjects in a field survey. In addition some 200 hospital materials were included in the prospective study. The results obtained provided the basis for the suggestions made concerning the different methods that can be applied to the future study of the prevalence of amoebiasis in any given population exposed to the risk of infection by Entamoeba histolytica. Local (Ibadan) strains of Entamoeba histolytica have been successfully cultured and the in-vitro characteristics studied. From the materials provi.ded by the in-vitro cultures of the organism, investigations have been made on E. histolytica antigens and the corresponding antibodies produced in man. The results of these investigations have been utilized in immunological studies, designed to define the mechanism of production of some of the problems posed by amoebic infections. The severity and high fatality of the disease in pregnancy and puerperium, was studied in detail. The observation that amoebiasis tends to be more severe and to have a higher mortality in pregnant and puerperal women was made only recently. At the time the present studies were planned, the association of pregnancy with severe amoebiasis had not been well established, and the mechanism for this association was unknown. It was, however, wall known that pregnant women were more liable to severe for-ms of certain other infectious diseases and it was considered possible that a similar mechanism might be operating in the case of amoebiasis. The present work confirms these clinical observations. Thus from the statistical analyses of the results of both the autopsy and prevalence studies, it became evident that the high fatality of amoebiasis during pregnancy and the early puerperium was not fortuitous but real. A fulminating type of lesion affecting the whole length of the large bowel is commoner in pregnant women and in those in the early puerperium dying of amoebiasis, than in any other cases of amoebiasis seen at autopsy. Furthermore, the biochemical and immunological studies help to throw some light on the mechanism of the selectivity of Infection by E. histolytical. These same results, also provide some explanation for the severity of amoebiasis during pregnancy and the allied states. The conclusions, support the hypothesis of lowered resistance to infectious diseases during pregnancy. Speculative submissions are, therefore, made on the defective immune mechanism occurring during pregnancy and the early puerperium. Thus, the inability of pregnant women to produce 'sufficient antibodies' to amoebic infections, demonstrated by the reactivity of the immunoglobulins in amoebiasis, confirms the suspicion of the existence of a derangement of host-defence mechanisms during pregnancy. This raises the hope and encourages future search for the specific serum agents) which may account for the deranged immune mechanism. On similar basis, the characterization of amoebic antigens together with that of the corresponding antibodies, offers a new field in the study of the immunopathology of amoebiasis. In conclusion, from the combined autopsy, prevalence, in-vitro experimental, biochemical, and immunological studies, it is submitted: 1. That the association of pregnancy with the severe form of amoebiasis at least, in this part of the world, is one of the perplexing problems posed by the disease. 2. That chronic amoebic infection is associated with the development of growth-inhibiting factors in the serum, for example, in patients with amoebic liver abscess. 3. That, on the contrary, growth promoting factors were demonstrated in the sera of pregnant/puerperal women with or without acute amoebic dysentery. 4. It is suggested that the severity of the disease in pregnant/puerperal women is a reflection of the derangement of immune response during pregnancy, with particular reference to the production of serum immunoglobulins.